The Influence Of Influencer Credibility and Price On Purchase Intention: A Study On Billionaire's Project's Fashion Products - Tarmidi, Didi; Mardhiyah, Adella Khairunnisa (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The more advanced the development of technology, the wider and easier information that can be sought by the public so that it can provide new information and even new behaviors, including buying behavior towards a product. Billionaires Project as a businessman in the Fashion Industry engaged in digital marketing must be sensitive to consumer buying behavior patterns, especially on things that can increase buyer interest. This research focuses on two variables owned by Billionaire's Project, namely The Credibility of Influencer Arief Muhammad and Price which is quite competitive in his class because it is not the cheapest nor the most expensive. The research methods used in this research are quantitative methods with descriptive types of research. Sampling is done with the nonprobability sampling technique used is purposive sampling with a total of 400 respondents who know billionaire's project fashion products. While the data analysis techniques used are descriptive analysis and multiple linear regression analysis. The results of the study based on descriptive analysis for influencer credibility variables are already in the category of very good at 88%, price variables are already in the category of very good at 89%, and the re-buy interest variable is already in the excellent category of 89%. Influencer credibility and price had a positive and significant effect on buying interest with a magnitude of influence of 30.3% and the remaining 69.7% influenced by other factors that were not studied.